Mesoscopic Mechanism of Permeability of Coal Rock Mass with Increasing Temperature in the Range of Room Temperature to 350°C. (10th August 2022) - Xie, Jianlin; Meng, Tao; Jin, Tingxu; Sun, Xiaoyuan
Abstract : Engineering research on geothermal development, underground gasification of coal, and heat-injection-enhanced coal bed gas extraction is gaining more and more attention from the international community, and therefore the study of permeability of coal rock bodies under the effect of temperature has become almost a hot spot in the research of rock mechanics and seepage mechanics. However, the relationship between temperature and permeability that has been seen in the literature is different, and the mechanism explanation varies greatly. In this paper, the following conclusions were obtained from an experimental study of the fine-scale structural evolution of coking coal and fine sandstone specimens, using an experimental research method of simultaneous image observation of the pore structure evolution of coal rock samples by online heating. (1) With the increase of temperature, the inner areas of coal and rock mass with both solid particles and pure pores are affected by temperature. The microscopic experiment shows that the gray level of the image changes greatly, that is, the changes in pores are also large. These pores are the roar pores in the coal and rock mass. (2) With the increase in temperature, the solid skeleton of the coal specimen will produce expansion deformation. On the one hand, this expansion deformation will increase the pores between some skeletons and increase the overall porosity of the specimen. On the other hand, it will also reduce the pore area and reduce the overall porosity of the specimen due to the intrusion of the solid skeleton into the adjacent pores. These two phenomena occur at the same time with the increase in temperature. The dominant mode is determined by the type of coal. The physical structure and temperature of the section are affected jointly. (3) When the temperature increases, the porosity of coking coal samples increases first and then decreases, and 180°C is the turning point. The fine sandstone sample shows the law of decreasing first and then increasing, and 210°C is the turning point. (4) When the temperature increases, the smaller the porosity of coal and rock samples, the specimen shows the intrusion of the solid skeleton into adjacent pores, that is, the porosity decreases. After the turning temperature, the porosity increases with the increase of temperature.